Status of Land Carrying Capacity for Agricultural and Environmental Sustainability in the Nusa Penida Tourism Area - Nyoman Sudipa (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Land resources are very important in supporting tourism activities. As a developing tourism area, Nusa Penida requires sufficient land resources. The increasing population and tourists have triggered new activities affecting land use patterns, negatively impacting land availability and agricultural sustainability. This study aims to calculate the availability, needs, and status of land-carrying capacity to support the sustainability of agriculture in the Nusa Penida Tourism Area until 2028. The research method uses a quantitative approach by collecting primary data obtained directly in the field, secondary data originating from previous research, and data originating from official sources. The result of the calculation of land requirements based on the ecological footprint is the number of inhabitants multiplied by the ecological footprint (gha/capita); the land requirement for 2020 is 49,849 people multiplied by 0.36958702, which is 17,724.283 hectares, while the availability of land in Nusa Penida is 9,894 hectares. This shows that the carrying capacity of land in Nusa Penida has exceeded the threshold or a deficit of 7,830.283 hectares. The area of land in Nusa Penida reaches 20,284 hectares. In contrast, the availability of land in Nusa Penida is based on calculations using the actual production of each type of commodity and the price of rice at the producer level, the unit price of each commodity at the producer level, and the productivity of rice in Nusa Penida is only 9,894 hectares. The projection of land needs until 2028 is 24,640 hectares, so the land carrying capacity in Nusa Penida is a deficit. The results of the calculation of land requirements based on the ecological footprint are 14,746.283 hectares, while the availability of land in Nusa Penida is 9,894 hectares. This shows that the land carrying capacity in Nusa Penida has a deficit of 12,374.283 hectares.